Diagnostic analysis of potential risks and security systems in rocket development as a supporter of the defense environment ecosystem - Donny Haryogi Ramadhan; Gunaryo, Gunaryo; Y.H. Yogaswara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
State defense is essentially all universal defense efforts which means involving all citizens, territories, and other national resources, as well as being prepared early by the government and held in a total, integrated, directed, and continuous manner to uphold state sovereignty, territorial integrity and the safety of the entire nation from all threats both from outside and from within. This research aims to diagnostically analyze the potential risks and safety systems in rocket development as a benchmarking and basic foothold in the growth of the weapons technology ecosystem. This research uses a qualitative approach method with a literature study approach. The results obtained are in the form of various potential risks which can provide failures and losses in rocket development. The safety system that is possible to implement by prioritizing the suitability found in Indonesian rocket development, is to review and ensure the stages of preparation, integration and testing (or similar) in rocket development.